أثر الاقتصاد على الاستقرار السياسي في ليبيا دراسة مقارنة مع مصر وتونس (خلال الفترة 2011 ـ 2017) - أم العز علي الفارسي, (Scientific Journal of University of Benghazi, 2020)
This working paper is based on the assumption that the improvement of the levels of economic performance in a country with its oil wealth, such as Libya, would put solutions to the country's political and security problems. This paper adopted the descriptive analysis approach and the comparative analysis to show the effect of the economy on the political stability of the countries of the so-called Arab Spring, and an attempt to understand the state of insecurity and the deterioration of living conditions that coincided with the transitional periods of the Libyan state, focusing on: Social and economic stability, Fairness in income distribution, Achieving full employment. The study concluded that the citizen in Libya suffers from a deterioration in the standard of living. The result of structural imbalances inherited in service institutions, especially economic sectors, has resulted in budget deficits and high rates of unemployment among young people, lack of transparency, widespread corruption, a complete breakdown of institutional requirements, political deficiencies, and a deteriorating security situation. This is what the rest of the Arab Spring suffers from, despite the fact that it has young, educated human capital. In addition to wealth, capabilities, and experiences at home and abroad that are able to carry out the development goals in these countries. The study concluded the need to reduce the transitional phase in these countries and achieve a democratic system of government that provides an economic climate that contributes to maximizing the benefits of the national wealth, especially in Libya.